Analisis Tingkat Error Sistem Pengaturan Salinitas Air Pembenihan Budidaya Udang Galah - Rachman, Syaiful iful; Indrasary, Yoenie; Wibowo, Sunu Hasta; Ahyadi, Zaiyan; Yohanes, Edy (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2017)
By applying regulatory system technology using a controller a built-in recovery medium can control equipment such as a solenoid valve, a water pump. Then the system was equipped with conductivity sensor that serves to monitor the value of parameters of water salinity and water flow sensor to determine the water volume, in this research to make a prototype of water hatchery regulation system 5 ppt while for the maintenance of prawn larvae 12 ppt, then analyzed against the system water volume error rate. Based on the result of the research, it was found that the error rate of the system that had been de-signed the tool testing shows the average error of salinity water volume in the experimental system on 5 ppt media for fresh water volume indicated the system had an average error of 0.26 liters, while the salt water volume of 5ppt that the system had an average error of 0.18 liters. Then the system error rate on 12 ppt media experimental result for fresh water volume indicated that the system had an average error of 0.18 liters, while salinity water volume indicated that the system had an average error of 0.14 liters. For further research it will be necessary to add a PID or Fuzzy control system to the error rate that will occur could be reduced.